The Operative Challenges of Advanced Renal Cell Carcinoma with Vena Cava Involvement: A Report of Three Cases - Muftau Jimoh Bioku; Abdulwaid Niran Saliu; Stephen Odunayo Ikuerowo; Olufunmilade Omisanjo; Julius Olusanmi Esho (Case Reports in Urology)
Surgical resection remains an important component in the care of advanced renal cell carcinoma (RCC). Some of the patients so managed had relief of symptoms and improved quality of life. However, palliative nephrectomies in late cases with vena cava involvement are not without challenges. An important factor to be considered for successful surgery is adequate vena cava management. We report in this paper three patients who had metastatic RCC. For over three decades now, researchers in Lagos had recorded the abysmal prognosis of advanced cases of RCC. Yet, late presentation and diagnosis still persisted in our environment. There is therefore the need to repackage our strategies aimed at early detection of this pathology and thus improved postoperative outcome.